2018
DOI: 10.1111/jir.12559
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition, shifting and updating in relation to psychometric intelligence across ability groups in the psychiatric population

Abstract: Background Assessment of intelligence and executive function (EF) is common in complex neuropsychiatric practice. Although previous studies have shown that EF and intelligence are related, it is unknown whether these constructs relate to one another in a similar manner across different ability groups (mild intellectual disability, borderline intellectual disability and normal/high intelligence). This study therefore examines the relation between three EFs (inhibition, shifting and updating) and intelligence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Processing speed is associated with both MDD (Austin et al, 2001;Sarapas et al, 2013) and set-shifting and inhibition, and many set-shifting or inhibition tasks are conducted under time constraint, meaning that processing speed can directly affect the measurement of setshifting and inhibition (Bessette et al, 2020). Similarly, measures of general intellectual functioning (e.g., full scale IQ [FSIQ]) are correlated with specific EF components such as setshifting and inhibition (e.g., Biesmans et al, 2019), and are also lower in individuals with MDD relative to healthy controls (Ahern and Semkovska, 2017). Therefore, studies that do not address processing speed or general intellectual functioning as potential confounds cannot disentangle whether deficits in set-shifting or inhibition performance are truly deficits in these processes or instead reflect deficits in processing speed or general cognitive functioning.…”
Section: Methodological Limitations Of Studies Of Neurocognitive Endophenotypes For Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Processing speed is associated with both MDD (Austin et al, 2001;Sarapas et al, 2013) and set-shifting and inhibition, and many set-shifting or inhibition tasks are conducted under time constraint, meaning that processing speed can directly affect the measurement of setshifting and inhibition (Bessette et al, 2020). Similarly, measures of general intellectual functioning (e.g., full scale IQ [FSIQ]) are correlated with specific EF components such as setshifting and inhibition (e.g., Biesmans et al, 2019), and are also lower in individuals with MDD relative to healthy controls (Ahern and Semkovska, 2017). Therefore, studies that do not address processing speed or general intellectual functioning as potential confounds cannot disentangle whether deficits in set-shifting or inhibition performance are truly deficits in these processes or instead reflect deficits in processing speed or general cognitive functioning.…”
Section: Methodological Limitations Of Studies Of Neurocognitive Endophenotypes For Depressionmentioning
confidence: 99%
“…As general intelligence is associated with set-shifting and inhibition (e.g., Biesmans et al, 2019), the Wechsler Test of Adult Reading (Holdnack, 2001) was used to estimate each participant's full-scale IQ (FSIQ). The WTAR asks participants to pronounce 50 irregularly spelled words, with each participant's raw score reflecting the number of words correctly pronounced.…”
Section: Wechsler Test Of Adult Readingmentioning
confidence: 99%
“…Low test performances in people with lower mental abilities (due to younger age, lower intelligence or neurological disorders) might thus reflect a (diminished) general ability (g) rather than specific cognitive impairment. The unity/diversity model seems to capture the organization of executive functions mainly in cognitively healthy adult populations, which may not be applicable in lower-ability groups (Biesmans et al, 2019;Janssen et al, 2013;Karr et al, 2018). Earlier studies that found a significant association between executive dysfunction and neuropsychiatric symptoms (Brodaty et al, 2012;McPherson et al, 2002) did not take general cognitive functioning into account and used executive measures that could be argued to be task impure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a measure of sustained (d2 sustained‐attention test) attention was obtained, as well as measures of executive functions that focus on planning and organization (subtasks “Key search” and “Zoo map” of the Behavioural Assessment of the Dysexecutive Syndrome for Children). Executive functioning refers to complex control mechanisms such as planning, shifting and monitoring that enable a person to perform effective, goal‐directed and self‐regulating behavior (Barkley, 2012; Biesmans, van Aken, Frunt, Wingbermühle & Egger, 2019; Lezak, Howieson, Tranel & Bigler, 2012; Salthouse, 2005). As for memory functioning, learning tasks with both auditory and visual stimuli were performed (Auditory Verbal Learning Test, Rey Complex Figure Test).…”
Section: Methodsmentioning
confidence: 99%